The principles of liver resection. Issue 8 (August 2020) - Vagg, Daniel; Toogood, Giles
Abstract: Liver resection offers the only potential for curative treatment for many primary and secondary hepatic malignancies. With ongoing advances in both surgical technique and postoperative management, the indications for surgery continue to expand; however, perioperative risk remains significant as increasingly complex cases are considered. The fundamental principle is to achieve complete resection of disease with preservation of an adequate functional liver remnant. Successful outcomes rely on detailed knowledge of both intra- and extrahepatic anatomy and demand meticulous attention to patient selection, surgical technique and perioperative care. This article reviews the essential considerations in contemporary hepatobiliary surgery.